**Simplify:**

[1/(√4 + √5)] + [1/(√5 + √6)] + [1/(√6 + √7)] + [1/(√7 + √8)] + [1/(√8 + √9)]

**Solution:**

Let us simplify individually,

[1/(√4 + √5)]

Rationalize the denominator, we get

[1/(√4 + √5)] = [1(√4 – √5)] / [(√4 + √5) (√4 – √5)]

= [(√4 – √5)] / [(√4)^{2} – (√5)^{2}]

= [(√4 – √5)] / [4 – 5]

= [(√4 – √5)] / -1

= -(√4 – √5)

Now,

[1/(√5 + √6)]

Rationalize the denominator, we get

[1/(√5 + √6)] = [1(√5 – √6)] / [(√5 + √6) (√5 – √6)]

= [(√5 – √6)] / [(√5)^{2} – (√6)^{2}]

= [(√5 – √6)] / [5 – 6]

= [(√5 – √6)] / -1

= -(√5 – √6)

Now,

[1/(√6 + √7)]

**Rationalize the denominator, we get**

[1/(√6 + √7)] = [1(√6 – √7)] / [(√6 + √7) (√6 – √7)]

= [(√6 – √7)] / [(√6)^{2} – (√7)^{2}]

= [(√6 – √7)] / [6 – 7]

= [(√6 – √7)] / -1

= -(√6 – √7)

Now,

[1/(√7 + √8)]

**Rationalize the denominator, we get**

[1/(√7 + √8)] = [1(√7 – √8)] / [(√7 + √8) (√7 – √8)]

= [(√7 – √8)] / [(√7)^{2} – (√8)^{2}]

= [(√7 – √8)] / [7 – 8]

= [(√7 – √8)] / -1

= -(√7 – √8)

Now,

[1/(√8 + √9)]

Rationalize the denominator, we get

[1/(√8 + √9)] = [1(√8 – √9)] / [(√8 + √9) (√8 – √9)]

= [(√8 – √9)] / [(√8)^{2} – (√9)^{2}]

= [(√8 – √9)] / [8 – 9]

= [(√8 – √9)] / -1

= -(√8 – √9)

**So, according to the question let us substitute the obtained values,**

[1/(√4 + √5)] + [1/(√5 + √6)] + [1/(√6 + √7)] + [1/(√7 + √8)] + [1/(√8 + √9)]

= -(√4 – √5) + -(√5 – √6) + -(√6 – √7) + -(√7 – √8) + -(√8 – √9)

= -√4 + √5 – √5 + √6 – √6 + √7 – √7 + √8 – √8 + √9

= -√4 + √9

= -2 + 3

= 1

**More Solution:**

- Find the value of x2 + 5xy + y2.
- Choose the correct statement:
- Between two rational numbers:
- The product of any two irrational numbers is:
- Which of the following is an irrational number?
- The following is an irrational number?
- A rational number between √2 and √3 is:
- The decimal expansion of the rational number:
- 2√3 + √3 is equal to: